A nanocomposite reflective insulation board and its preparation process

By using the superposition structure of aluminum foil and composite aerogel insulation plate in the composite insulation plate, and adding tin oxide antimony coating and Te-doped Mg2Si material to the composite insulation plate, the problem of poor infrared barrier effect at high temperatures is solved, and efficient infrared barrier and low thermal conductivity are achieved.

CN119329139BActive Publication Date: 2025-03-25HENAN DEFA REFRACTORY MATERIALS CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411855867.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-03-25
Estimated Expiration
2044-12-17

AI Technical Summary

Technical Problem

The existing composite insulation plates have low heat transfer performance under the temperature environment of high-temperature molten furnace body, especially the low efficiency of infrared radiation blocking in the 2-8μm band, resulting in a decrease in heat insulation effect.

Method used

Nanocomposite reflective insulation plates are prepared by sequentially applying and superposition of aluminum foil, composite aerogel insulation plate, inorganic grid cloth, composite aerogel insulation plate, and inorganic grid cloth. The composite insulation agent is added to the composite insulation agent to improve the infrared barrier effect through the dual effects of multiple reflection and infrared radiation absorption.

Benefits of technology

The infrared barrier effect of nanocomposite reflective insulating plate at high temperatures is significantly improved, with a barrier rate of more than 83.9%, and a thermal conductivity coefficient of less than 0.11W/m·K, enhancing the thermal insulation and insulation performance of the molten iron furnace body.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119329139B_ABST
    Figure CN119329139B_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of thermal insulation materials, and specifically discloses a nano-composite reflective thermal insulation board and its preparation process. The nano-composite reflective thermal insulation board is formed by gluing and stacking aluminum foil, composite aerogel thermal insulation board, inorganic mesh cloth, composite aerogel thermal insulation board, and inorganic mesh cloth in this order. The composite aerogel thermal insulation board is made of the following raw materials in parts by weight: 50-55 parts of silica nano-aerogel powder, 1.5-2.5 parts of composite thermal insulation agent, 2-3 parts of Kevlar chopped fibers, 2-2.5 parts of phenolic emulsion, and 1 part of silane coupling agent; the preparation steps of the composite thermal insulation agent are as follows: first, a wrinkled GO template is constructed, and tellurium-doped Mg is obtained through the wrinkled GO template. 2 Si pleated sheet material, and then through the slurry impregnation and heat treatment to finally get the composite insulation agent. The prepared nano composite reflective insulation board is applied to the ladle furnace body, which can significantly enhance the infrared radiation blocking ability and thermal insulation effect of the ladle furnace body.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of thermal insulation materials, and more specifically, to a nano-composite reflective thermal insulation board and a preparation process thereof. Background Art

[0002] Nano insulation board is a board made of various materials and processes based on nano principle. It is widely used in the lining structure of furnaces in metallurgy, chemical industry, ceramics and other industries to reduce heat loss in furnaces and improve energy efficiency.

[0003] At present, the main raw material of nano insulation board on the market is nano silica aerogel. Nano silica aerogel is very suitable for making insulation materials due to its nano porous structure and extremely low thermal conductivity. In industry, it is usually combined with high temperature resistant fiber cloth and metal foil to make composite insulation board with better insulation performance. This composite insulation board has a relatively excellent effect on inhibiting heat transfer inside and outside the ladle / iron ladle furnace. However, for some special ladle furnace temperature environments, its heat transfer inhibition performance is not high, and even declines. In particular, after some raw material iron is melted to form molten iron, after special process treatment, the temperature inside the ladle furnace can reach more than 1800℃. Under this temperature condition, the heat transfer in the furnace is mainly near-mid-infrared thermal radiation of 2-8μm. Although the radiation can be partially blocked by the working layer and permanent layer of the ladle furnace lining, the heat volume reaching the composite insulation board is still large, and a large amount of infrared radiation will continue to be transmitted to the outer layer of the furnace body through the composite insulation board in various forms. SiO2 aerogel in composite insulation board can block infrared radiation, but the efficiency of blocking infrared radiation in the 2-8μm band is low, which makes the insulation effect of composite insulation board significantly reduced under high temperature of molten iron ladle. In order to block as much infrared radiation as possible, it is usually necessary to add sunscreen to composite insulation board. At present, the types of sunscreen are mainly absorption sunscreen and reflection sunscreen, but the combination of the two sunscreens with both absorption and reflection has not been studied.

[0004] The Chinese patent application document with application publication number CN105347798A discloses a ceramic fiber heat insulation board. By adding nano-titanium dioxide components into ceramic fibers, the heat inside the furnace body is used to promote the transformation of the nano-titanium dioxide crystal phase to anatase and rutile, thereby obtaining a crystal structure with a certain infrared reflection effect, and using this structure to improve the traditional heat insulation board.

[0005] The above application documents utilize the transformation of nano-titanium dioxide crystal phases at different temperatures to improve the infrared shielding ability of the insulation board. However, this crystal phase transformation depends on the stability of the furnace temperature, and in actual industrial production, the furnace temperature does not remain constant. According to different process requirements, the furnace temperature will increase or decrease. According to the operations in the above invention application, nano-titanium dioxide cannot effectively play its role under certain temperature conditions. In addition, the infrared shielding effect of nano-titanium dioxide is mainly reflected in the energy band of its crystal phase. The transformed crystal phase does not have a significant absorption effect on 2-8μm infrared radiation. Therefore, there is still a need to find a composite insulation board with high infrared blocking effect. Summary of the invention

[0006] In order to further improve the infrared blocking effect of the composite reflective plate at high temperature, the present application provides a nano-composite reflective insulation plate and a preparation process thereof.

[0007] In a first aspect, the present application provides a nano-composite reflective insulation board, which is formed by applying glue and laminating in the order of aluminum foil, composite aerogel insulation board, inorganic mesh cloth, composite aerogel insulation board, and inorganic mesh cloth, wherein the composite aerogel insulation board is made of the following raw materials in parts by mass: 50-55 parts of silica nano-aerogel powder, 1.5-2.5 parts of composite insulation agent, 2-3 parts of Kevlar chopped fibers, 2-2.5 parts of phenolic emulsion, and 1 part of silane coupling agent;

[0008] The preparation of the composite thermal insulation agent comprises the following steps:

[0009] (1) Graphene oxide, a supramolecular crosslinker and water are mixed, subjected to ultrasonic treatment at elevated temperature, and cooled to obtain a GO hydrogel; the GO hydrogel is then coated on a pre-stretched 3M elastic adhesive, fixed by heat baking, and the graphene oxide layer is peeled off after cooling, and the wrinkled GO template with a wrinkled morphology is obtained by grinding;

[0010] (2) dissolving and dispersing the wrinkled GO template, adjusting the pH, adding ethyl orthosilicate solution, filtering after the reaction, washing the precipitate, drying and then grinding, mixing the product with magnesium powder and tellurium powder in a porcelain crucible, calcining in a tubular furnace, and removing impurities to obtain tellurium-doped Mg2Si wrinkled sheet material;

[0011] (3) adding nano-tin oxide powder and nano-antimony trioxide powder into a mixed solvent, and obtaining an impregnation slurry after ultrasonic treatment;

[0012] (4) Putting the tellurium-doped Mg2Si wrinkled sheet material into the impregnation slurry, impregnating it three times, and obtaining a composite thermal insulation agent after precipitation heat treatment.

[0013] Through the above technical scheme, the prepared composite thermal insulator has two effects. First, when the infrared radiation of the furnace body reaches the nano-composite reflective insulation board, the infrared radiation can be reflected by the tin antimony oxide coating structure on the outer surface of the composite thermal insulator, and multiple reflections can be achieved through the wrinkled morphology structure. Through this reflection effect, part of the infrared radiation can be blocked from continuing to escape outside the furnace. On the other hand, Mg2Si, which serves as the skeleton of the composite thermal insulator, can absorb infrared radiation itself. Through Te doping treatment, the Mg2Si energy band can be adjusted to cover the 2-8μm area of ​​the infrared radiation of the furnace body. This further prevents the infrared radiation heat energy of the furnace body from being lost to the outside. Through the effects of multiple reflections and radiation absorption, the rate of heat loss in the furnace body is reduced.

[0014] Preferably, in step (1), the supramolecular crosslinking agent is prepared by mixing polyvinyl alcohol, polyvinyl pyrrolidone and propylene glycol methyl ether in a mass volume ratio of (3-8) g:(3-5) g:(1-2) mL.

[0015] By adopting the above technical solution, the addition of supramolecular crosslinking agent can promote the gelation process of graphene oxide. Among the supramolecular crosslinking agents, propylene glycol methyl ether plays a dispersing role. The long chains of polyvinyl alcohol and polyvinyl pyrrolidone can provide a gel growth skeleton for graphene oxide and accelerate the gelation process. At the same time, the oxygen-rich functional groups on polyvinyl alcohol and polyvinyl pyrrolidone can couple with the carboxyl and epoxy groups on the surface of graphene oxide, thereby obtaining a more stable gel structure, which is helpful for subsequent template processing.

[0016] Preferably, in step (1), the pre-stretching ratio of the 3M elastic glue pre-stretching treatment is 80%-95%.

[0017] By adopting the above technical solution, an elastic substrate suitable for wrinkling graphene oxide can be obtained. When the elastic glue is pre-stretched, a retractable deformation will be generated, and the elastic glue can slowly shrink over time. After applying GO hydrogel, the curing of GO hydrogel and the shrinkage of the elastic substrate are carried out simultaneously, and finally a wrinkled GO template can be obtained.

[0018] Preferably, in step (2), the dripping speed of the ethyl orthosilicate solution is 5 mL / min.

[0019] By adopting the above technical scheme, the process of hydrolysis of ethyl orthosilicate and the growth of SiO2 formed by hydrolysis on the wrinkled GO template can be regulated. Avoid the cementation of ethyl orthosilicate and the uneven growth of SiO2. The hydrolysis of ethyl orthosilicate obtains a polyhydroxy structure centered on silicon atoms. The π electron cloud in the hydroxy structure forms π-π conjugation with the large π bond on graphene oxide, which reduces the energy barrier for the growth of silicon dioxide on graphene oxide. By regulating the dripping speed of ethyl orthosilicate, the SiO2 formed by hydrolysis can be uniformly precipitated, thereby obtaining a higher quality silicon-based structure.

[0020] Preferably, in step (2), the calcination temperature is set to 600-700° C. and the calcination time is 2-3 hours.

[0021] By adopting the above technical solution, under high temperature conditions, SiO2 and Mg undergo redox reaction in a mixed protective gas (the mixed protective gas is a mixture of argon with a volume fraction of 75.5% and hydrogen with a volume fraction of 24.5%). The reaction that occurs can be specifically expressed as: , and finally magnesium silicide is obtained. By adjusting the calcination temperature and time, magnesium silicide with a more complete structure can be obtained.

[0022] Preferably, in step (2), the protective gas used is a mixture of argon with a volume fraction of 75.5% and hydrogen with a volume fraction of 24.5%.

[0023] By adopting the above technical solution and introducing hydrogen into the protective gas, the side reaction of thermal reduction of silicon dioxide by magnesium to obtain silicon can be reduced, thereby obtaining magnesium silicide with higher purity.

[0024] Preferably, in step (3), the average particle size of the nano-tin oxide powder is 30-50 nm, and the average particle size of the nano-antimony trioxide powder is 20-25 nm.

[0025] By adopting the above technical scheme, the impregnation slurry prepared by using nano tin oxide powder and nano antimony trioxide powder of the above particle size is more delicate. After impregnation and subsequent heat treatment of tellurium-doped Mg2Si wrinkled sheet material, a coating with higher glossiness can be obtained, which helps to enhance the reflective ability of the composite insulation agent.

[0026] Preferably, in step (3), the mass ratio of nano-tin oxide powder to nano-antimony trioxide powder is 10:(0.8-1).

[0027] By adopting the above technical solution, the obtained impregnation slurry has the best effect.

[0028] Preferably, in step (4), the heat treatment temperature is 650-700° C. and lasts for 2-3 hours.

[0029] By adopting the above technical solution, heat treatment can cover a layer of tin-antimony coating structure with a certain gloss on the surface of the tellurium-doped Mg2Si wrinkled sheet material, and the prepared composite insulation agent has the best effect of reflecting and absorbing infrared band thermal radiation.

[0030] In a second aspect, the present application provides a process for preparing a nanocomposite reflective insulation board, comprising the following steps:

[0031] (SO1) a composite thermal insulation agent, silica nano-aerogel powder, Kevlar chopped fibers, phenolic emulsion, and silane coupling agent are mixed, added into water, stirred, vacuum filtered to obtain a wet plate, and air-dried to obtain a composite aerogel plate;

[0032] (SO2) The layers of board materials are glued and stacked in the order of aluminum foil-composite aerogel board-inorganic mesh cloth-composite aerogel board-inorganic mesh cloth, subjected to temperature treatment, and then pressed at room temperature for 1-2 days. After cutting, a nano-composite reflective insulation board is obtained.

[0033] Preferably, the average thickness of the aluminum foil is 8 μm.

[0034] Through the above technical solution, the obtained nano-composite reflective insulation board can still maintain low thermal conductivity. Aluminum foil itself is a highly thermally conductive material, but when its thickness is reduced to between 6-10μm, due to its micron-level size effect, the degree of obstruction to the propagation of light and heat radiation on its surface is increased, and the thermal conductivity of the aluminum foil itself is greatly reduced. In addition, the use of aluminum foil material on the outer surface of the nano-composite reflective insulation board can also use the mirror reflection of the aluminum foil surface to reflect part of the heat radiation back to the furnace body, thereby reducing the heat loss in the ladle furnace body.

[0035] In summary, this application has the following beneficial effects:

[0036] 1. The present application prepares a composite thermal insulation agent, and the nano-composite reflective insulation board prepared by adding the composite thermal insulation agent has a strong absorption and reflection effect on 2-8μm infrared radiation in the ladle furnace.

[0037] 2. When the nano-composite reflective insulation board in the present application is applied to the ladle furnace body, the near-mid-infrared light radiated by the furnace body is dissipated in the nano-composite reflective insulation board layer through two ways without being transmitted to the outside. First, when the infrared radiation reaches the composite insulation agent, since the thermal radiation still follows the reflection and refraction rules, most of the infrared radiation will be dissipated or reflected back to the furnace body by multiple reflections in the folded structure, and the evenly deposited antimony tin oxide mirror layer can also enhance the reflection effect. For a small amount of infrared radiation that passes through antimony tin oxide, it is effectively absorbed by Mg2Si in the interlayer. Through the dual effects of reflection and absorption, the thermal radiation of the ladle furnace body under high temperature is weakened, thereby enhancing the thermal insulation and heat preservation effect of the ladle furnace body as a whole.

[0038] 3. The nano-composite insulation board prepared by the composite insulation agent of the present application has a blocking rate of more than 83.9% for infrared radiation in the ladle furnace, and the thermal conductivity of the prepared nano-composite reflective insulation board at 1000°C is lower than 0.11 W / m·K. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 Schematic diagram of the structure of the prepared nanocomposite reflective insulation board.

[0040] Figure 2 The infrared radiation intensity and infrared radiation blocking rate of the ladle furnace body with the nano-composite reflective insulation board built into it in Example 1-3 and Comparative Example 1-2.

[0041] Figure 3 The temperature change of molten iron in the ladle furnace with nano-composite reflective insulation board built in in Example 1-3 and Comparative Example 1-2 for 2 hours. DETAILED DESCRIPTION

[0042] In the present embodiment 1-3 and the comparative example 1-2, the structure of the prepared nanocomposite reflective insulation board is as follows: Figure 1 shown.

[0043] Example 1

[0044] In this embodiment, the nano-composite reflective insulation board is made of aluminum foil, composite aerogel insulation board and inorganic mesh cloth in the order of aluminum foil, composite aerogel insulation board, inorganic mesh cloth, composite aerogel insulation board and inorganic mesh cloth. The composite aerogel insulation board is made of the following raw materials by weight: 500g of silica nano-aerogel powder, 15g of composite insulation agent, 20g of Kevlar chopped fiber, 25g of phenolic emulsion, and 10g of silane coupling agent KBM-303;

[0045] The preparation steps of the composite thermal insulation agent of this embodiment are as follows:

[0046] (1) 0.3g of graphene oxide (3μm), 3g of polyvinyl alcohol, 5g of polyvinyl pyrrolidone, and 1mL of propylene glycol methyl ether were mixed and dissolved in 90mL of deionized water. The mixture was treated at 75℃ for 15h, and the ultrasonic power was controlled to 0.5kW for 25min. After cooling, GO hydrogel was obtained. 3M elastic glue was prepared and cut into 55mm×90mm size as an elastic substrate. Then, the elastic substrate was pre-stretched along the width direction with a pre-stretching ratio of 80%. Then, the adhesive surface was attached to a rectangular frame made of a 110mm×95mm iron wire hoop, and the GO hydrogel was applied to the elastic glue backing position with a scraper. The coating thickness was controlled to be 500μm, and then it was sent to an oven for drying at 45℃ for 2h. The solidified layer was peeled off to obtain a wrinkled GO template with a wrinkled morphology.

[0047] (2) The wrinkled GO template was dissolved in a mixed solution of 125 mL of deionized water and anhydrous ethanol. The pH was adjusted to 8.5, the temperature was 35 °C, and the magnetic stirring speed was controlled to 50 rpm. Then, 20 mL of a 5% mass fraction of ethyl orthosilicate solution was added to the system at a rate of 5 mL / min. The reaction was continued for 4 h to obtain a cross-linked SiO2 product grown with graphene as a template. The precipitate was filtered and washed, vacuum dried at 35 °C for 30 min, and then ground in a mortar for 2 min to obtain a product named A1. A1 was mixed evenly with 0.8 g of magnesium powder (1 μm) and 0.001 g of Te in a porcelain crucible and then flattened with a spatula. After calcination at 600 °C for 2 h in a mixed protective gas environment, impurities were removed by pyrolysis to obtain a tellurium-doped Mg2Si wrinkled sheet material.

[0048] (3) Mix 0.1 g of nano-tin oxide powder (30 nm) and 0.01 g of nano-antimony trioxide powder (20 nm), disperse the mixture in 25 mL of a mixed solvent, control the ultrasonic power to 1 kW, and perform ultrasonic treatment for 20 min to obtain an impregnation slurry.

[0049] (4) The tellurium-doped Mg2Si wrinkled sheet material is impregnated into the impregnation slurry at a temperature of 45°C for 25 minutes, the precipitate is filtered out, dried at 50°C for 10 minutes, and then re-immersed into the impregnation slurry for a second impregnation. The operation is repeated, and after the third impregnation is completed, the precipitate is transferred to a muffle furnace and heat-treated at a temperature of 650°C for 2 hours to obtain a composite thermal insulation agent.

[0050] The steps for preparing the nanocomposite reflective insulation board in this embodiment are as follows:

[0051] (S01) Add composite insulation agent, silica nano-aerogel powder, Kevlar chopped fibers, phenolic emulsion and silane coupling agent KBM-303 into 450 mL of deionized water. Set the stirring speed to 200 rpm and stir for 30 min to obtain a uniform mixture. Then, vacuum filter the mixture to obtain a wet plate with a thickness of 5 mm. The wet plate is air-dried at 45 ° C for 20 h to obtain a composite aerogel plate.

[0052] (S02) The board layers are stacked in the order of aluminum foil-composite aerogel board-inorganic mesh cloth-composite aerogel board-inorganic mesh cloth. Deionized water is mixed with a high-temperature resistant inorganic adhesive to prepare a glue solution with a mass fraction of 15% of the high-temperature resistant inorganic adhesive, and the glue solution is used to evenly apply glue between the board layers for bonding. The water in the adhesive is evaporated by treating it at 75°C for 3 hours. Then it is transferred to a room temperature environment and pressed for 1 day, and finally a nano-composite reflective insulation board is obtained.

[0053] Among them, graphene oxide (TNIGO, purity > 97%) was provided by Chengdu Organic Chemistry Co., Ltd., Chinese Academy of Sciences. The mixed solution of deionized water and anhydrous ethanol was prepared by mixing deionized water and anhydrous ethanol in a volume ratio of 10:1. The mixed protective gas was mixed by argon with a volume fraction of 75.5% and hydrogen with a volume fraction of 24.5%. The mixed solvent was prepared by anhydrous ethanol: deionized water: dispersant sodium hexametaphosphate in a mass ratio of 150:50:1. Silica nano aerogel powder was provided by Sichuan Xinyun New Materials Technology Co., Ltd. High temperature resistant inorganic adhesive (model: ZS-107) was provided by Beijing Zhisheng Weihua Chemical Co., Ltd. Kevlar chopped fiber (1.5 dtex, average length 1 mm) was provided by Guangdong Teweilong New Materials Application Co., Ltd. Aluminum foil (model: 1060, thickness 8 μm) was provided by Henan Mingtai Aluminum Co., Ltd. Inorganic mesh cloth was provided by Renqiu Boda Industry and Trade Glass Fiber Products Co., Ltd.

[0054] Example 2

[0055] In this embodiment, the nano-composite reflective insulation board is made of aluminum foil, composite aerogel insulation board and inorganic mesh cloth in the order of aluminum foil, composite aerogel insulation board, inorganic mesh cloth, composite aerogel insulation board and inorganic mesh cloth. The composite aerogel insulation board is made of the following raw materials by weight: 550g of silica nano-aerogel powder, 20g of composite insulation agent, 25g of Kevlar chopped fiber, 25g of phenolic emulsion, and 10g of silane coupling agent KBM-303;

[0056] The preparation steps of the composite thermal insulation agent of this embodiment are as follows:

[0057] (1) 0.3g of graphene oxide (5μm), 5g of polyvinyl alcohol, 3g of polyvinyl pyrrolidone, and 2mL of propylene glycol methyl ether were mixed and dissolved in 100mL of deionized water. The mixture was treated at 75℃ for 15-20h, and the ultrasonic power was controlled to 0.5kW for 30min. After cooling, GO hydrogel was obtained. 3M elastic glue was prepared and cut into 55mm×90mm size as an elastic substrate. Then, the elastic substrate was pre-stretched along the width direction with a pre-stretching ratio of 85%. Then, the adhesive surface was attached to a rectangular frame made of a 110mm×95mm iron wire hoop, and the GO hydrogel was applied to the back adhesive position of the elastic glue with a scraper. The coating thickness was controlled to be 500μm, and then it was sent to an oven for drying at 45℃ for 2h. The solidified layer was peeled off to obtain a wrinkled GO template with a wrinkled morphology.

[0058] (2) The wrinkled GO template was dissolved in a mixed solution of 125 mL of deionized water and anhydrous ethanol. The pH was adjusted to 8, the temperature was 35 °C, and the magnetic stirring speed was controlled to 50 rpm. Then, 20 mL of a 5% mass fraction of ethyl orthosilicate solution was added to the system at a rate of 5 mL / min. The reaction was continued for 5 h to obtain a cross-linked SiO2 product grown with graphene as a template. The precipitate was filtered and washed, vacuum dried at 35 °C for 20 min, and then ground in a mortar for 1 min. The obtained product was recorded as A2. A2 was mixed evenly with 0.8 g of magnesium powder (1 μm) and 0.001 g of Te in a porcelain crucible and then flattened with a spatula. The mixture was calcined at 675 °C for 2 h under a mixed protective gas environment. After pyrolysis to remove impurities, a tellurium-doped Mg2Si wrinkled sheet material was obtained.

[0059] (3) Mix 0.125 g of nano-tin oxide powder (40 nm) and 0.01 g of nano-antimony trioxide powder (25 nm), disperse them in 25 mL of mixed solvent, control the ultrasonic power to 1.5 kW, and ultrasonicate for 20 min to obtain an impregnation slurry.

[0060] (4) The tellurium-doped Mg2Si wrinkled sheet material was impregnated into the impregnation slurry at a temperature of 45°C for 20 minutes, the precipitate was filtered out, dried at 60°C for 10 minutes, and then re-immersed into the impregnation slurry for a second impregnation. The operation was repeated, and after the third impregnation was completed, the precipitate was transferred to a muffle furnace and heat-treated at 680°C for 2.5 hours to obtain a composite thermal insulation agent.

[0061] The steps for preparing the nanocomposite reflective insulation board in this embodiment are as follows:

[0062] (S01) Add composite insulation agent, silica nano-aerogel powder, Kevlar chopped fiber, phenolic emulsion and silane coupling agent KBM-303 into 500 mL of deionized water. Set the stirring speed to 200 rpm and stir for 30 min to obtain a uniform mixture. Then vacuum filter the mixture to obtain a wet plate with a thickness of 5 mm. The wet plate is air-dried at 45 ° C for 20 h to obtain a composite aerogel plate.

[0063] (S02) The board layers are stacked in the order of aluminum foil-composite aerogel board-inorganic mesh cloth-composite aerogel board-inorganic mesh cloth. Deionized water is mixed with a high-temperature resistant inorganic adhesive to prepare a glue solution with a mass fraction of 15% of the high-temperature resistant inorganic adhesive, and the glue solution is used to evenly apply glue between the board layers for bonding. The water in the adhesive is evaporated by treating it at 75°C for 3 hours. Then it is transferred to a room temperature environment and pressed for 2 days to finally obtain a nano-composite reflective insulation board.

[0064] Among them, graphene oxide (TNIGO, purity > 97%) was provided by Chengdu Organic Chemistry Co., Ltd., Chinese Academy of Sciences. The mixed protective gas was a mixture of argon with a volume fraction of 75.5% and hydrogen with a volume fraction of 24.5%. The mixed solution of deionized water and anhydrous ethanol was prepared by deionized water and anhydrous ethanol in a volume ratio of 10:1. The mixed solvent was prepared by anhydrous ethanol: deionized water: dispersant sodium hexametaphosphate in a mass ratio of 200:100:1. Silica nano aerogel powder was provided by Sichuan Xinyun New Materials Technology Co., Ltd. The high temperature resistant inorganic adhesive (model: ZS-107) was provided by Beijing Zhisheng Weihua Chemical Co., Ltd. Kevlar chopped fiber (1.5 dtex, average length 1 mm) was provided by Guangdong Teweilong New Materials Application Co., Ltd. Aluminum foil (model: 1060, thickness 8 μm) was provided by Henan Mingtai Aluminum Co., Ltd. The inorganic mesh cloth was provided by Renqiu Boda Industry and Trade Fiberglass Products Co., Ltd.

[0065] Example 3

[0066] In this embodiment, the nano-composite reflective insulation board is made of aluminum foil, composite aerogel insulation board and inorganic mesh cloth in the order of aluminum foil, composite aerogel insulation board, inorganic mesh cloth, composite aerogel insulation board and inorganic mesh cloth. The composite aerogel insulation board is made of the following raw materials by weight: 550g of silica nano-aerogel powder, 25g of composite insulation agent, 30g of Kevlar chopped fiber, 20g of phenolic emulsion, and 10g of silane coupling agent KBM-303;

[0067] The preparation steps of the composite thermal insulation agent of this embodiment are as follows:

[0068] (1) 0.3g of graphene oxide (10μm), 8g of polyvinyl alcohol, 5g of polyvinyl pyrrolidone, and 1.5mL of propylene glycol methyl ether were mixed and dissolved in 100mL of deionized water. The mixture was treated at 80℃ for 16h, and the ultrasonic power was controlled to 0.5kW for 25min. After cooling, GO hydrogel was obtained. 3M elastic glue was prepared and cut into 55mm×90mm size as an elastic substrate. Then, the elastic substrate was pre-stretched along the width direction with a pre-stretching ratio of 95%. Then, the adhesive surface was attached to a rectangular frame made of a 110mm×95mm iron wire hoop, and the GO hydrogel was applied to the elastic glue backing position with a scraper. The coating thickness was controlled to 500μm, and then it was sent to an oven for drying at 50℃ for 3h. The solidified layer was peeled off to obtain a wrinkled GO template with a wrinkled morphology.

[0069] (2) The wrinkled GO template was dissolved in a mixed solution of 125 mL of deionized water and anhydrous ethanol. The pH was adjusted to 8.5, the temperature was 35 °C, and the magnetic stirring speed was controlled to 50 rpm. Then, 30 mL of 5% ethyl orthosilicate solution was added to the system at a rate of 5 mL / min. The reaction was continued for 6 h to obtain a cross-linked SiO2 product grown with graphene as a template. The precipitate was filtered and washed, vacuum dried at 35 °C for 30 min, and then ground in a mortar for 2 min. The obtained product was recorded as A3. A3 was mixed evenly with 0.8 g of magnesium powder (1 μm) and 0.001 g of Te in a porcelain crucible and then flattened with a spatula. After calcination at 700 °C for 3 h in a mixed protective gas environment, impurities were removed by pyrolysis to obtain a tellurium-doped Mg2Si wrinkled sheet material.

[0070] (3) Mix 0.1 g of nano-tin oxide powder (50 nm) and 0.01 g of nano-antimony trioxide powder (25 nm), disperse them in 30 mL of mixed solvent, control the ultrasonic power to 1.5 kW, and ultrasonicate for 25 min to obtain an impregnation slurry.

[0071] (4) The tellurium-doped Mg2Si wrinkled sheet material was impregnated into the impregnation slurry at a temperature of 50°C for 25 minutes, the precipitate was filtered out, dried at 65°C for 15 minutes, and then re-immersed into the impregnation slurry for a second impregnation. The operation was repeated, and after the third impregnation was completed, the precipitate was transferred to a muffle furnace and heat-treated at 700°C for 3 hours to obtain a composite thermal insulation agent.

[0072] The steps for preparing the nanocomposite reflective insulation board in this embodiment are as follows:

[0073] (S01) Add composite insulation agent, silica nano-aerogel powder, Kevlar chopped fibers, phenolic emulsion and silane coupling agent KBM-303 into 550 mL of deionized water. Set the stirring speed to 200 rpm and stir for 30 min to obtain a uniform mixture. Then, vacuum filter the mixture to obtain a wet plate with a thickness of 5 mm. The wet plate is air-dried at 45 ° C for 20 h to obtain a composite aerogel plate.

[0074] (S02) The board layers are stacked in the order of aluminum foil-composite aerogel board-inorganic mesh cloth-composite aerogel board-inorganic mesh cloth. Deionized water is mixed with a high-temperature resistant inorganic adhesive to prepare a glue solution with a mass fraction of 15% of the high-temperature resistant inorganic adhesive, and the glue solution is used to evenly apply glue between the board layers for bonding. The water in the adhesive is evaporated by treating it at 75°C for 5 hours. Then it is transferred to a room temperature environment and pressed for 2 days to finally obtain a nano-composite reflective insulation board.

[0075] Among them, graphene oxide (TNIGO, purity > 97%) was provided by Chengdu Organic Chemistry Co., Ltd., Chinese Academy of Sciences. The mixed protective gas was a mixture of argon with a volume fraction of 75.5% and hydrogen with a volume fraction of 24.5%. The mixed solution of deionized water and anhydrous ethanol was prepared by deionized water and anhydrous ethanol in a volume ratio of 10:1.5. The mixed solvent was prepared by anhydrous ethanol: deionized water: dispersant sodium hexametaphosphate in a mass ratio of 100:50:1. Silica nano aerogel powder was provided by Sichuan Xinyun New Materials Technology Co., Ltd. High temperature resistant inorganic adhesive (model: ZS-107) was provided by Beijing Zhisheng Weihua Chemical Co., Ltd. Kevlar chopped fiber (1.5 dtex, average length 1 mm) was provided by Guangdong Teweilong New Materials Application Co., Ltd. Aluminum foil (model: 1060, thickness 8 μm) was provided by Henan Mingtai Aluminum Co., Ltd. Inorganic mesh cloth was provided by Renqiu Boda Industry and Trade Fiberglass Products Co., Ltd.

[0076] Comparative Example 1

[0077] The difference between this comparative example and Example 3 is that the tellurium-doped Mg2Si wrinkled sheet material is not impregnated, and the remaining steps are the same as Example 3.

[0078] Comparative Example 2

[0079] The difference between this comparative example and Example 3 is that an equal amount of high-purity titanium dioxide (model: JWN-TO-3N01, purity 99.9%) is used instead of the composite thermal insulation agent, and the remaining steps are the same as Example 3.

[0080] Performance testing

[0081] Thermal conductivity test

[0082] Refer to the test sample preparation method for insulation board for ingot casting in ZBQ45008 and YB / T059-1994 "Test method for thermal conductivity of insulation board (boiling plate method)". Place the treated nano-composite reflective insulation board lining at the bottom of the calorimeter heating furnace, and fill the empty part at the bottom with refractory fiber. Fill the calorimeter heating furnace with deionized water that occupies 2 / 3 of the furnace volume, and then heat the lining at a rate of 10-15℃ / min, so that the temperature of the lining heating surface reaches 1000℃ and burns until smokeless, and keeps warm for 20 minutes. Collect the condensed water at the exhaust port of the calorimeter and weigh it. The thermal conductivity of the nano-composite reflective insulation board is calculated by the following formula.

[0083]

[0084] λ: thermal conductivity of nanocomposite reflective insulation board, W / (m·k);

[0085] G: condensed water mass, g;

[0086] t2: hot surface temperature of nanocomposite reflective insulation board, °C;

[0087] t1: cold surface temperature of nanocomposite reflective insulation board, °C;

[0088] a: thickness of nanocomposite reflective insulation board, mm;

[0089] τ: water receiving time, min.

[0090] Table 1 Thermal conductivity of nanocomposite reflective insulation boards of Examples 1-3 and Comparative Examples 1-2

[0091]

[0092] Furnace temperature and infrared radiation test

[0093] A 15 mm thick nanocomposite insulation board prepared in the embodiment and comparative example was built into the ladle furnace. Then 1600°C molten iron was filled and left to stand for 2 hours for testing. An infrared thermometer (model: NP15LR) was used to measure the change of the molten iron temperature in the furnace within 2 hours, and the temperature data was recorded. A digital infrared radiometer (model: RLK601) was used to detect the infrared radiation intensity inside and outside the furnace when it was stable, and the infrared radiation value measured inside the furnace was used as a reference to calculate the infrared blocking rate of the infrared radiation after passing through the furnace barrier material.

[0094] By analyzing Examples 1-3 and Comparative Examples 1-2 and combining with Table 1, it can be seen that the thermal conductivity of the nanocomposite reflective insulation board prepared using the composite insulation agent is at a low level, but the thermal conductivity is lower than that of Comparative Example 1. This may be because the process of obtaining the coating by dipping in the examples introduces metal components, which increases the thermal conductivity of the nanocomposite reflective board.

[0095] Analyze Examples 1-3 and Comparative Examples 1-2 and combine Figure 2 It can be seen that the nano-composite reflective insulation board prepared using the composite insulation agent has the best infrared radiation blocking effect, and by comparing Examples 1-3 with Comparative Example 1, it can be concluded that the infrared blocking ability of the composite insulation agent can be further enhanced by impregnating the tellurium-doped Mg2Si corrugated sheet material with a coating.

[0096] Analyze Examples 1-3 and Comparative Examples 1-2 and combine Figure 3 It can be seen that the nano-composite reflective insulation board prepared using the composite insulation agent is applied to the ladle furnace body. After 2 hours of standing, the temperature of the molten iron in the ladle can still be stabilized at above 1500°C, and the thermal insulation performance is excellent.

[0097] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A nanocomposite reflective insulation board, characterized in that: The composite aerogel insulation board is made of aluminum foil, composite aerogel insulation board, inorganic mesh cloth, composite aerogel insulation board, and inorganic mesh cloth, and the composite aerogel insulation board is made of the following raw materials in parts by mass: 50-55 parts of silica nano aerogel powder, 1.5-2.5 parts of composite insulation agent, 2-3 parts of Kevlar chopped fibers, 2-2.5 parts of phenolic emulsion, and 1 part of silane coupling agent; The preparation of the composite thermal insulation agent comprises the following steps: (1) Graphene oxide, a supramolecular crosslinker and water are mixed, subjected to ultrasonic treatment at elevated temperature, and cooled to obtain a GO hydrogel; then the GO hydrogel is coated on a 3M elastic adhesive with a pre-stretching ratio of 80%-95%, fixed by heat baking, and after cooling, the graphene oxide layer is peeled off and ground to obtain a wrinkled GO template with a wrinkled morphology; the supramolecular crosslinker is prepared by mixing polyvinyl alcohol, polyvinyl pyrrolidone and propylene glycol methyl ether in a mass volume ratio of (3-8) g:(3-5) g:(1-2) mL; (2) dissolving and dispersing the wrinkled GO template, adjusting the pH, adding ethyl orthosilicate solution, filtering after reaction, washing the precipitate, drying and grinding, mixing the product with magnesium powder and tellurium powder in a porcelain crucible, placing it in a tube furnace, adjusting the temperature to 600-700°C, calcining for 2-3h under mixed protective gas conditions, and removing impurities to obtain tellurium-doped Mg2Si wrinkled sheet material; the mixed protective gas is a mixture of argon with a volume fraction of 75.5% and hydrogen with a volume fraction of 24.5%; (3) adding nano-tin oxide powder and nano-antimony trioxide powder into a mixed solvent, and obtaining an impregnation slurry after ultrasonic treatment; (4) Putting the tellurium-doped Mg2Si wrinkled sheet material into the impregnation slurry, impregnating it three times, and obtaining a composite thermal insulation agent after precipitation heat treatment.

2. The nanocomposite reflective insulation board according to claim 1, characterized in that: In the step (2), the dropping speed of the ethyl orthosilicate solution is 5 mL / min.

3. The nanocomposite reflective insulation board according to claim 1, characterized in that: In the step (3), the average particle size of the nano-tin oxide powder is 30-50 nm, and the average particle size of the nano-antimony trioxide powder is 20-25 nm.

4. The nanocomposite reflective insulation board according to claim 1, characterized in that: In the step (3), the mass ratio of nano-tin oxide powder to nano-antimony trioxide powder is 10:(0.8-1).

5. The nanocomposite reflective insulation board according to claim 1, characterized in that: In the step (4), the heat treatment temperature is 650-700°C and lasts for 2-3 hours.

6. A process for preparing the nanocomposite reflective insulation board as claimed in claim 1, characterized in that: The steps include: (SO1) a composite thermal insulation agent, silica nano-aerogel powder, Kevlar chopped fibers, phenolic emulsion, and silane coupling agent are mixed, added into water, stirred, vacuum filtered to obtain a wet plate, and air-dried to obtain a composite aerogel plate; (SO2) The layers of board materials are glued and stacked in the order of aluminum foil-composite aerogel board-inorganic mesh cloth-composite aerogel board-inorganic mesh cloth, subjected to temperature treatment, and then pressed at room temperature for 1-2 days. After cutting, a nano-composite reflective insulation board is obtained.

7. The process for preparing a nanocomposite reflective insulation board according to claim 6, characterized in that: In the (SO2) step, the average thickness of the aluminum foil is 8 μm.

Citation Information

Patent Citations

  • Ceramic fiber heat insulation plate

    CN105347798A

  • Preparation method of graphene-like magnesium silicide nanosheets

    CN104261411A

  • Graphene heat dissipation coating and preparation method thereof

    CN115558327A

  • Ultra-light aerogel-based vacuum insulation panel and preparation method thereof

    CN115677270A

  • Fire prevention heat decorative integration plate

    CN204781734U